Assessment on the Fermentation Quality and Bacterial Community of Mixed Silage of Faba Bean With Forage Wheat or Oat - Li, Hongliang; Zeng, Tairu; Du, Zhaochang; Dong, Xintan; Xin, Yafen; Wu, Yushan; Huang, Linkai; Liu, Lin; Kang, Bo; Jiang, Dongmei; Wu, Bihua; Yang, Wenyu; et al. (Frontiers in Microbiology, 2022)
Faba bean (Vicia faba L.), although as a kind of high-quality and high-yield forage, could hardly achieve the great quality of silage because of the high buffering capacity. Mixed silage of faba bean with oat (Avena sativa L.) or forage wheat (Triticum aestivum L.) at different ratios could improve the fermentation quality and bacterial community. Compared with 100% faba bean silage (BS), mixed silage improved the fermentation quality, not only increased lactic acid production and reduced pH, but reduced the production of propionic acid and ammonia nitrogen. The chemical compositions of faba bean with forage wheat (BT) mixed silage was better than that of faba bean with oat (BO) mixed silage, and that of the mixing ratios of 3:7, 5:5 (fresh weight) mixed silage were better than 1:9. However, the fermentation quality of BO mixed silage were better than those of BT mixed silage, and that of 3:7 mixed silage (BO30) was the optimal. Analysis of bacterial community showed that mixed silage increased the relative abundance of lactic acid bacteria after ensiling, and the relatively high abundance of Lactobacillus showed the inhibitory effects on the proliferation of Serratia and Hafnia_Obesumbacterium, so that it alleviated the negative effects on silage and stabilized the fermentation quality. This present study exhibited that mixed silage of faba bean with oat or forage wheat not only had significant effects on chemical compositions and fermentation process of materials, but modified bacterial community so that improved the fermentation quality effectively. The mixed silage of 30% faba bean with 70% oat (BO30) is recommended in the faba bean mixed silage.